Mapping service capabilities using ISM and fuzzy DEMATEL - Tingting Li; Dan Lv; Davod Khosroanjom (Scientific Reports)
Abstract In the present competitive landscape, small enterprises (SEs) must consistently strive to enhance and sustain their position by utilizing suitable capabilities. Recognizing such advancements is mostly linked to service capabilities and resources. Nonetheless, there is a lack of research focused on evaluating service capabilities in isolation or from a purely functional perspective to ascertain the criteria associated with service capabilities in small firms supported by hybrid methodologies. Consequently, employing the resource-based view (RBV), the current study examined the links among these criteria and analyzed their interdependencies and strengths. The present study utilized interpretive structural modeling (ISM) and fuzzy decision-making trial and evaluation laboratory (fuzzy DEMATEL) methodologies for this objective. The findings indicated that the criterion analysis and formulation of the strategy is of greater significance than other criteria. The research findings about service capacities are examined for practical insights.